Sistem Pendukung Keputusan Menentukan Kualitas Ayam Petelur Menggunakan Metode Simple Additive Weighting - Supiyandi, Supiyandi; Hariyanto, Eko; Rizal, Chairul; Zen, Muhammad; Pasaribu, Saddam Husen Romadon (Forum Kerjasama Pendidikan Tinggi, 2022)
Determining the selection of quality laying hens is a decision that must be carried out so that production results will increase and the quality of the eggs produced, there are lots of criteria that must be owned for the complexity and importance of the problem requiring analytical methods rather than intuitive decisions. as a condition for obtaining the scholarship. Each laying hens must have criteria to determine the quality of laying hens. Decision Support System Determining the Quality of Laying Hens with the Simple Additive Weighting (SAW) Method is an element that greatly influences the smooth running of the task. The division in this study will be appointed a case, namely looking for the best alternative based on predetermined criteria using the SAW (Simple Additive) method. Weighting) The research was conducted by finding the weight value for each attribute, then a ranking process was carried out which would determine the optimal alternative, namely the best quality laying hens.